Caracterización de los sistemas agroforestales cafetaleros de los productores asociados a Coopesarapiquí R. L. en la zona norte de Costa Rica - Barrantes-Valverde, Luis Andrés (Instituto Tecnológico de Costa Rica, 2015)
This work was performed in the Northern Zone of Costa Rica in order to characterize the shape, conformation and some major agronomic components of coffee agroforestry systems, besides establishing both an economic and systematic comparison of the two agricultural, traditional methods and agroforestry. For this analysis, 22% of those associated with Coopesarapiquí RL was selected by a non-probabilistic sampling was applied and an analysis tool based on four pillars that are the farm, the crop (coffee), type of Shadow used and the economic component within the system, complemented by a tour on the farm that supports the analysis with respect to the observations lived throughout the process. Within results, a list of the species most used as shade coffee farms associated to Coopesarapiquí RL, where legumes are the largest presence in more than 50% representation was obtained different handlings applied in the sampled farms and major cost management and production of coffee to their collection, plus differences and similarities between the sampled farms in the North Zone and three farms that coffee tradition zones were established
Proyecto de graduación (Bachillerato en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronegocios, 2015
Keywords: Café; Agroforestería; Componentes agronómicos